Emblem and Membership certificate of the National Union of Gas Workers and General Labourers of Great Britain and Ireland, 1890 (1890)
1880-1914 "Emblem and Membership certificate of the National Union of Gas Workers and General Labourers of Great Britain and Ireland, 1890" [T0510.jpg], 1890